Podcast Sebagai Media Literasi Hukum: Analisis Podcast Sebagai Media Dalam Memahami Nilai-Nilai Bela Negara Oleh Generasi Muda di Indonesia - Sheila, Eirene Eva Marta; Fadilah, Fatma Putri; Putri, Maria Sylvia; Nuhi, Muhammad Hanan; Jeconia Hia, Javier Artarindo; Manullang, Halim; Tampubolon, Bona J.; Keppy, Christmas Petra; Puspitarini, Nabilah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In today’s digital era, legal literacy among young people remains relatively low, despite the increasing accessibility of digital media. This article aims to analyze how podcasts can serve as an effective medium for legal literacy, particularly in promoting awareness of national defense values. This study adopts a qualitative method with a content analysis approach. The data source is taken from the podcast episode on the Endgame YouTube channel featuring Prof. Mahfud MD as a guest speaker. Data collection was conducted through a listening and note-taking technique to identify key legal and national messages conveyed in the podcast. The results show that podcasts are capable of delivering legal and national issues with a casual yet substantial communication style, making the content more accessible and relevant to young audiences. Moreover, podcasts encourage listeners to think critically, participate actively, and foster a sense of justice and legal awareness. Therefore, podcasts have the potential to serve as alternative media for enhancing legal literacy and strengthening national defense consciousness in the digital era.